Transportation access and health service utilization: A cross-sectional study in Maccini Ayo Hamlet, Jeneponto Regency - Surahmawati, Surahmawati; Arranury, Zilfadhilah; Hasanah, Andi Nida’ul; Aisyah, Nabila Salsabilah; Azmi, Sinta Ulul (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
The utilization of health services in rural Indonesia remains suboptimal, with a significant proportion of households not accessing health care facilities despite available infrastructure. Previous studies have largely overlooked the nuanced role of transportation in facilitating or hindering access to care in remote areas. This study aimed to identify factors associated with the utilization of health services in Maccini Ayo Hamlet, Bontomanai Village, Jeneponto Regency. A quantitative, cross-sectional study was conducted among all household heads (n=59) in the study area. Data were analyzed using the Chi-Square test to determine associations between selected socio-demographic and accessibility variables and health service utilization. The study found a statistically significant association between the type of vehicle used and the utilization of health services (p=0.000). Conversely, no significant associations were found for age, educational attainment, occupation, income, travel distance, travel time, or health insurance ownership. These findings underscore the pivotal role of transportation access in influencing health-seeking behavior in rural settings. Enhancing mobility infrastructure could thus be a strategic focus for public health interventions aimed at increasing healthcare access in similar regions